Are customers happy? a study of satisfaction in Sarawak’s fast-food restaurants - Thien, Nancy Swee Yen; Latip, Malisah (USIM Press, 2024)
Fast food restaurants play a significant role in contemporary dining culture, offering convenience and quick service to customers. Understanding the factors that contribute to customer satisfaction and happiness within this sector is crucial for both businesses and researchers. Customer satisfaction in fast food restaurants is often influenced by various factors such as perceived price, service quality, food quality, and the physical environment of the premises. This study investigated the determinants of customer satisfaction and happiness towards fast food restaurants in Sarawak, Malaysia. Data from 414 respondents aged 18 and above were analysed using SPSS through Spearman’s correlation and simple linear regression analysis. The findings showed that all variables, perceived price, service quality, food quality, and physical environment quality had significant correlations with customer satisfaction. Customer satisfaction was also found to influence customer happiness positively. The results of this study show that the best method to increase customer satisfaction is to offer a fair price and improve the quality of the service, food, and physical environment of the premises. All these factors consequently affect customer happiness with fast food restaurants. These findings provide valuable insights into customer perceptions and behaviour in the fast-food sector in Sarawak. Identifying key determinants of satisfaction and happiness offers the basis for strategic decision-making and service improvement initiatives to optimize the dining experience for consumers.